The Effect of Endurance Exercise on Semen Quality in Male Athletes: A Systematic Review - Alex Aerts; Annelien Temmerman; Arne Vanhie; Dirk Vanderschueren; Leen Antonio (Sports Medicine - Open, 2024)
Abstract Background Endurance exercise has the potential to affect reproductive function, with amenorrhea in female athletes. However, most studies focus on women. Evidence on the association between endurance exercise and male fertility is limited. Objective To synthesise existing literature on exercise-induced alterations in semen parameters and to assess the clinical impact on male fertility. Methods Studies reporting on the association between semen parameters and endurance exercise in healthy men were eligible. Men attending fertility clinics were excluded. We searched MEDLINE (PubMed), Embase, SPORTDiscus, Cochrane Central Register of Controlled Trials (CENTRAL), ClinicalTrials.gov and International Clinical Trials Registry Platform (ICTRP) from their inception to May 28th 2022. JBI Critical Appraisal Tool was used to assess the potential risk of bias. Results Thirteen studies met inclusion criteria, reporting on 280 subjects. Eight articles reported on endurance runners, three on cyclists and four on triathletes. Four studies did not find any statistically significant sperm alterations. Five reported significant changes in semen parameters, but these were not clinically relevant, as semen parameters remained well above World Health Organisation (WHO) thresholds. Four articles reported a decrease in semen quality with potential clinical consequences as they found a reduced number of sperm cells exhibiting normal morphology in cyclists and triathletes and a greater amount of DNA fragmentation in triathletes. Conclusion Endurance exercise can have a negative effect on semen quality, although rarely with a clinically relevant impact on male fertility. Evidence is however limited, with poor quality of the included studies. Registration: PROSPERO International prospective register of systematic reviews (CRD42022336753).